2020
DOI: 10.1002/suco.202000011
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study to evaluate the postfire mechanical properties of concrete specimens

Abstract: In this research, the mechanical behavior of structural concrete made with materials in Iran has been experimentally investigated after experiencing high temperatures. For this purpose, six different mix designs were selected in accordance with Iranian Concrete Standard (ABA). Six different target temperatures (25, 100, 250, 500, 700, and 900°C) were also selected for the purpose of fire experience. Compressive and tensile strength tests were carried out on all of the samples and their behavior was evaluated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Yu et al 42 investigated the effect of single‐sized and hybrid steel fibers in the ultra‐high performance conventional concrete and reported that the hybrid steel fibers are more efficient for improving the energy dissipation capacity of concrete under impact load. Saedi et al 43 reported that the mixture containing steel fiber had a better performance in all temperatures; its reduction pace was slower compared to other mix design until 700°C and showed more strength. Sayyad and Patankar 44 investigated the effect of steel fibers on the mechanical properties of GPC.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al 42 investigated the effect of single‐sized and hybrid steel fibers in the ultra‐high performance conventional concrete and reported that the hybrid steel fibers are more efficient for improving the energy dissipation capacity of concrete under impact load. Saedi et al 43 reported that the mixture containing steel fiber had a better performance in all temperatures; its reduction pace was slower compared to other mix design until 700°C and showed more strength. Sayyad and Patankar 44 investigated the effect of steel fibers on the mechanical properties of GPC.…”
Section: Introductionmentioning
confidence: 99%